Alzheimer's disease detection combining novel radiogenomics of APOE e, structural and functional MRI - Suppiah, Subapriya; Seriramulu, Vengkatha Priya; Ibrahim, Buhari; Ibrahim, Nur Shahidatul Nabila (Organization for Human Brain Mapping, 2024)
Structural T1 weighted and functional MRI correlated with APOE e testing for developing a radiogenomics framework for improved detection of Alzheimer's disease